Teachers' Perceptions About Climate Change: A Comparative Study of Public and Private Schools and Colleges in Bangladesh - Ahmed, Mufti Nadimul Quamar; Ahmed, Khandaker Jafor; Chowdhury, Mohammed Thanvir Ahmed; Atiqul Haq, Shah Md (Frontiers in Climate, 2022)
This study examines school and university teachers’ perceptions about climate change, taking into account socio-demographic aspects, academic backgrounds, and experiences with the impacts of climate change. The study included 95 teachers from three schools and colleges (two private and one public) in the city of Sylhet, Bangladesh. The results show that most teachers have heard about climate change and understand what it means. Most also perceive that temperatures in Bangladesh are rising or fluctuating and that rainfall is falling or fluctuating. The chi-squared test shows that teachers’ perceptions about climate change depend on whether their educational institution is private or public and whether they believe their region is at risk of extreme weather events (EWE). Binary and multinomial logistic regressions were used to specifically examine the impact of teachers’ socio-demographic and academic backgrounds and their previous experiences with extreme weather events on their perceptions about climate change. The results of the binary logistic regression show that educational institution type and the sections in which the teacher teaches are two significant predictors of teachers’ perceptions about temperature change. The multinomial logistic regression analysis of perceptions about changes in precipitation shows that there is a statistically significant effect for factors including type of educational institution, undergraduate courses taught, areas vulnerable to EWEs, and environment- or climate-change-related courses taken.